HARMONISASI IDENTITAS BUDAYA DAN MODERNITAS: STUDI KASUS PADA PERPUSTAKAAN WILAYAH SOEMAN HS, PROVINSI RIAU - Dewi Astuti; Rakhmanita Rakhmanita; Sumaiyah Fitriandini (Jurnal Teknik dan Science, 2023)
The Soeman HS Regional Library in Riau Province not only serves as a place for book collections, but also as a center for information and cultural identity. This research uses exploratory methods and qualitative case studies to identify the architectural identity of this library that combines modern and traditional concepts. This building creates the impression of an open book, highlighting its function as a source of knowledge, with a façade that reflects Malay identity and the style of Riau Province. This study highlights the way elements of regional identity is presented in functional buildings and their application to modern buildings. Data were collected through observation, documentation, and literature study. The library's identity as a source of knowledge is emphasized through the form of book-like buildings and folklore reliefs in the outer hallway. As offices, glass facades and formal workspaces reflect modernity and efficiency. Malay culture is reflected through the roof of Rehal Al-Quran and wajik motifs on the façade of the building. The study illustrates how the elements blend harmoniously, creating a place of knowledge that embraces cultural heritage. The conclusion of this study emphasizes the importance of identity in the design of functional buildings that respect local culture.